Pharmacokinetic and bioequivalence study of etoricoxib tablet in healthy Bangladeshi volunteers - Shohag, Md. Hasanuzzaman; Islam, Mohammad Safiqul; Ahmed, Maizbha Uddin; Joti, Jafreen Jamal; Islam, Md. Siddiqul; Hasanuzzaman, Md.; Hasnat, Abul (Arzneimittelforschung, 2011)
The aim of this study was to compare the pharmacokinetic properties of two etoricoxib (CAS 202409-33-4) 60 mg formulations, namely Etocox-60® (test product) and reference product, and to evaluate whether these two formulations meet the FDA criteria to assume bioequivalence. Twenty-four healthy volunteers were enrolled into this randomized, single-dose, 2-way crossover, open-label pharmacokinetic study. Subjects were randomly assigned to receive the test formulation followed by the reference formulation or vice versa as a single dose of 60 mg tablets after 12 h overnight fasting, with a washout period of two weeks. Following oral administration, blood samples were collected at 0 (baseline), 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 6.0, 8.0, 10.0, 12.0, 24.0, 48.0, 72.0, 96.0, and 120.0 h. Serum concentration of etoricoxib was assessed using a high performance liquid chromatographic-UV spectrometry procedure. The pharmacokinetic parameters were determined by the non-compartmental method. After administering a single dose of 60 mg of each etoricoxib formulation, the obtained mean (SD) values for the test and reference products were 1.26 (0.33) and 1.29 (0.35) µg/ml for Cmax; 3.25 (2.64) and 2.63 (1.40) h for tmax; 29.63 (8.31) and 30.40 (5.85) h · µg/ml for AUC0–120; and 31.84 (10.97) and 33.00 (8.10) h · µg/ml for AUC0–∞, respectively. The mean t1/2 was found 27.99 (7.87) h and 29.84 (7.93) h for test and reference product respectively. From paired t-test, no significant differences were observed (p > 0.05) for any pharmacokinetic parameters. After analysis of variance, no period, sequence or formulation effects were observed for any pharmacokinetic property. The 90% confidence intervals of the test/reference mean ratios of the In-transformed AUC0–120, AUC0–∞ and Cmax mean values were 95.90% (85.37% – 107.74%), 94.69% (84.43% – 106.20%) and 97.87% (85.54%–111.98%), respectively, which fell within the predetermined FDA bioequivalence range of 80% – 125%. This single-dose study found that the test and reference formulations of etoricoxib met the regulatory criteria for bioequivalence in terms of both rate and extent of absorption.
Keywords: Bangladeshi volunteers; Bioequivalence; Etoricoxib; Non-steroidal anti-inflammatory drug; Pharmacokinetics